The Ministry : the inside story of Japan's Ministry of Finance - Hartcher, Peter (London : HarperCollins Business, 1998)
An account of how Japan's Ministry of Finance maintains control of the nation's economy illustrating how the Ministry has been instrumental in the downfall of two prime ministers, and examining how the lives of its workforce are strictly controlled. Hartcher also considers the possible consequences of the Ministry's actions.
Includes bibliographical references (pages 265-293) and index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid
Keywords: Japan -- Okurasho; Japan -- Economic policy -- 1945-; Japan -- Politics and government